1996
DOI: 10.1037/0882-7974.11.2.342
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood deterioration and self-rated health in later life.

Abstract: This study examined the relationship between the physical living environment and self-rated health in later life. It is hypothesized that older adults who reside in deteriorated neighborhoods will report more physical health problems than elderly people who live in better physical environments. However, it is further predicted that these effects will only emerge in the most dilapidated living conditions. Data from a nationwide survey of older adults provide support for this complex nonlinear relationship. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 48 publications
4
66
0
2
Order By: Relevance
“…Physical factors that may be of relevance for well-being include noise and pollution, heightened stress and risks for accidents, or inadequate sanitation (see Krause, 1996). In a similar vein, the Disablement Process model (Verbrugge & Jette, 1994) proposes that extra-individual factors in the physical or built environment can make a profound difference in whether or not functional limitations result in disability.…”
Section: Socialmentioning
confidence: 99%
“…Physical factors that may be of relevance for well-being include noise and pollution, heightened stress and risks for accidents, or inadequate sanitation (see Krause, 1996). In a similar vein, the Disablement Process model (Verbrugge & Jette, 1994) proposes that extra-individual factors in the physical or built environment can make a profound difference in whether or not functional limitations result in disability.…”
Section: Socialmentioning
confidence: 99%
“…22,23 Lowerextremity functioning loss has been associated with neighborhoods' excessive noise, inadequate lighting, and heavy traffic, 24 and living in dilapidated living environments is associated with modest decreases in ADLs. 18 Studies also have found associations between muscle strength, 56 mobility difficulties, 57 disability, 58 physical functioning, 59 and hip fracture-related mortality 60 with area socioeconomic factors. In terms of the specific importance of an area's economic conditions to individuals' health, Robert 61 found that areas of lower socioeconomic status (eg, percentage of families earning ‡ $30,000, an area's unemployment percentage) had fewer social services, senior centers, and mental health services, and residency in those areas was associated with individuals' numbers of chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…23 Also, functional limitations have been linked to an area's excessive noise, inadequate lighting, and heavy traffic, 24 while residency in dilapidated environments is associated with decreases in activities of daily living (ADLs). 18 ADL limitations are associated with a decreased likelihood of older adults leaving home and going into town, 25 while individuals with, compared to those without, impaired ADLs have twice the risk of a fall. 26 Balance and gait limitations, which may increase with less activity, are also fall risk predictors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations